2016
DOI: 10.1007/s00190-016-0981-y
|View full text |Cite
|
Sign up to set email alerts
|

Space-Wise approach for airborne gravity data modelling

Abstract: Regional gravity field modelling by means of remove-compute-restore procedure is nowadays widely applied in different contexts: it is the most used technique for regional gravimetric geoid determination, and it is also used in exploration geophysics to predict grids of gravity anomalies (Bouguer, free-air, isostatic, etc.), which are useful to understand and map geological structures in a specific region. Considering this last application, due to the required accuracy and resolution, airborne gravity observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Usually the very-high frequencies are removed. To give an example: let examine a grid of gravity anomalies from a global gravity field model up to degree 2190; it is well known that the maximum spatial resolution achievable is around 10 km half-wavelength [34]. Now, a DTM used to compute the Bouguer anomalies from such a global model should be chosen in such a way that its gravitational effect has a similar spatial resolution.…”
Section: Data Reductionmentioning
confidence: 99%
“…Usually the very-high frequencies are removed. To give an example: let examine a grid of gravity anomalies from a global gravity field model up to degree 2190; it is well known that the maximum spatial resolution achievable is around 10 km half-wavelength [34]. Now, a DTM used to compute the Bouguer anomalies from such a global model should be chosen in such a way that its gravitational effect has a similar spatial resolution.…”
Section: Data Reductionmentioning
confidence: 99%
“…The former research has shown that the shortcoming of using a model to correct the error is that the model usually has constant deviation, when it is compared with the truth data in a certain area [27]. However, this shortcoming could be largely eliminated by ground gravimetry and upward extension or by using satellite-only model [28]. Thus, the forward and backward fusion method is divided into four steps, the scheme of which is shown in Figure 8: Use the forward algorithm to get gravity disturbance result,Use the backward algorithm to get gravity disturbance result,Correct the low frequency error by high precision global gravity field model,Fuse the data according to Equations (10) and (11).…”
Section: Applying Backward Navigation Algorithm To Improve Strapdomentioning
confidence: 99%
“…It is in fact well known that the gravimeter observations are affected from biases and trends. However, we will suppose in the current work that the observations, biases, and trends (for sufficiently long paths, i.e., more than 80 km) can be proficiently repaired by exploiting information coming from satellite observations as shown in [15]. As a consequence, we are entitled to apply also this second approximation in the following.…”
Section: Methodsmentioning
confidence: 99%
“…The final objective of this project is the definition of a procedure to optimally plan the airborne survey, according to the required final accuracy and spatial resolution. Thus, once the signal had been simulated, the processing technique described in [15] is applied, thus recovering the expected filtered gravitational field, together with its predicted accuracy. The whole methodology used to process the simulated signal is summarized here for the sake of completeness; however, the interested reader can refer to the already cited [15].…”
Section: Methodsmentioning
confidence: 99%